Silver ions are responsible for memory impairment induced by oral administration of silver nanoparticles. (15th June 2018) - Węsierska, M.; Dziendzikowska, K.; Gromadzka-Ostrowska, J.; Dudek, J.; Polkowska-Motrenko, H.; Audinot, J.N.; Gutleb, A.C.; Lankoff, A.; Kruszewski, M.
Highlights: Oral silver nanoparticle administration resulted in silver accumulation in brain. AgNPs cause impairment of long-term memory which engages cognitive coordination. Hippocampus is one of the most susceptible to Ag accumulation of the brain structures. Ag ions play a crucial role in induction of memory impairment. Abstract: Increasing use of silver nanoparticles (AgNPs) results in increased human exposure. AgNPs are able to cross brain-blood barrier and are a risk factor for the brain. Thus, we hypothesized that AgNPs exposure might affect hippocampal dependent memory, which required cognitive coordination processes. To verify the assumption, in this study we evaluated the effects of orally administered bovine serum albumin (BSA)-coated AgNPs on spatial memory, which engage cognitive coordination processes for on-going stimuli segregation. Rats following 28 days of oral administration with 1 mg/kg (n = 10) or 30 mg/kg (n = 10) BSA-AgNPs or saline, a control groups (n = 10, n = 8), were tested with an active place avoidance task in the Carousel Maze test. The study revealed significant impairment of long- and short-term memory, irrespectively of dose of AgNPs, whereas non-cognitive activity was on a similar level. We found significantly higher content of silver in the hippocampus in comparison to the lateral cortex. No silver was found in the cerebellum and the frontal cortex. The nanoSIMS analysis reveal a weak signal of silver in the hippocampus of AgNPs treated animals that should be attributed to the presence of silver in ionic form rather than AgNPs. Our findings indicate that oral exposure to a low dose AgNPs induces detrimental effect on memory and cognitive coordination processes. The presence of silver ions rather than AgNPs in different brain regions, in particular the hippocampus, suggests crucial role of silver ions in AgNPs-induced impairment of the higher brain functions.